2000
DOI: 10.1021/ja0017099
|View full text |Cite
|
Sign up to set email alerts
|

Supercontraction and Backbone Dynamics in Spider Silk:  13C and 2H NMR Studies

Abstract: The high-performance mechanical properties of certain spider silks can be radically altered by the addition of water. For example, unconstrained silk fibers from the major ampullate gland of the golden orbweaving spider, Nephila claVipes, contract to about half of their original length when immersed in water. In this paper we use solid-state 13 C and 2 H NMR to study N. claVipes silk fibers, so as to address the molecular origins of supercontraction in the wet silk. Using 13 C NMR, we study backbone dynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
217
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(240 citation statements)
references
References 40 publications
23
217
0
Order By: Relevance
“…The effects of hydration decrease the intensity of most of the peaks except for the two Ala peaks, Ala C α and Ala C β (β-sheet), which are generally attributed to the poly-Ala located in the β-sheet crystal-forming blocks. The overall intensity decrease of the spectra in the hydrated sample is thought to result from the increasing mobility of the protein backbone and side-chain mobility with hydration [22,23]. Of the affected peaks, the largest intensity drops were observed for the glycine (Gly) C α , and glutamate or glutamine (both labeled as Glx), serine (Ser) and proline (Pro) peaks.…”
Section: Neat (Ambient) and Hydrated Silkmentioning
confidence: 99%
“…The effects of hydration decrease the intensity of most of the peaks except for the two Ala peaks, Ala C α and Ala C β (β-sheet), which are generally attributed to the poly-Ala located in the β-sheet crystal-forming blocks. The overall intensity decrease of the spectra in the hydrated sample is thought to result from the increasing mobility of the protein backbone and side-chain mobility with hydration [22,23]. Of the affected peaks, the largest intensity drops were observed for the glycine (Gly) C α , and glutamate or glutamine (both labeled as Glx), serine (Ser) and proline (Pro) peaks.…”
Section: Neat (Ambient) and Hydrated Silkmentioning
confidence: 99%
“…This process is important to ensure the rigidity of the spider's web during its lifetime and is thought to be caused by the organization and arrangement of individual silk proteins. 53,54 Spider silk vs insect silk. Spider silk is often compared to insect silk, preferably taken from the silkworm Bombyx mori.…”
Section: Gpggx/gpgqq [Iii] Ggx (X = a S Or Y) And [Iv]mentioning
confidence: 99%
“…Interestingly, Jelinski and coworkers determined that super contraction of major ampullate dragline-silk of N. clavipes, corresponded to the consensus sequence, YGGLGS(N)QGAGR. 54 Additionally, it was suggested that substitution to an analogous, but less hydrophilic sequence might attenuate the contraction of silk in water. The engineered CRGD-silk sequence incorporates the YGGLGSQG repeat sequence, which corresponds to the indicated modification, and suggests a possible explanation for our observation.…”
Section: Topology and Fold Of The Crgd-silk Mimeticmentioning
confidence: 99%